Interfacial Assemble of Prussian Blue Analog to Access Hierarchical FeNi (oxy)-Hydroxide Nanosheets for Electrocatalytic Water Splitting - Hong, Jinquan; Lv, Jiangquan; Chen, Jialing; Cai, Lanxin; Wei, Mengna; Cai, Guoseng; Huang, Xin; Li, Xiaoyan; Du, Shaowu (Frontiers in Chemistry, 2022)
Developing facile methods for the synthesis of active and stable electrocatalysts is vitally important to realize overall water splitting. Here we demonstrate a practical method to obtain FeNiOOH nanosheets on Ni foam (NF) as bifunctional electrocatalyst by growing a FeCo Prussian blue analogue with further in situ oxidation under ambient conditions. The binder-free, self-standing FeNiOOH/NF electrode with hierarchical nanostructures requires low overpotentials of 260 mV and 240 mV at current density of 50 mA cm–2 for oxygen evolution reaction and hydrogen evolution reaction, respectively, in 1.0 M KOH solution. Therefore, an alkaline water electrolyzer constructed by bifunctional FeNiOOH/NF electrode as both anode and cathode delivers 50 mA cm–2 under a cell voltage of 1.74 V with remarkable stability, which outperform the IrO2-Pt/C-based electrolyzer. The excellent performance could be ascribed to the superior FeNiOOH intrinsic activity and the hierarchical structure. This work provides a cost-efficient surface engineering method to obtain binder-free, self-standing bifunctional electrocatalyst on commercial Ni foam, which could be further extended to other energy and environment applications.